Bhikkhuni And Gender Equality In The Vihara Dharmakirti Palembang (Al-Adyan: Journal of Religious Studies, 2021)
Gender equality remains a focus point of discourse to continue to be studied and is always associated with religious teachings, including Buddhism. The Buddha taught that women can play an active role in religious rituals and social activities. However, speculations by both religious leaders and Buddhists themselves take second place to women, lower than men. Therefore, this article focuses on explaining how gender equality is in the perspective of⁹ Buddhism and how the existence of Bhikkhuni at Vihara Dharmakirti Palembang is. This field research uses interviews, observations and documentation to obtain the necessary data. The results of this study indicate that the concept of gender equality in Buddhism is not contained in a clear text but the universal teachings of love serve as guidelines. The teaching of love for all creatures, especially humans, emphasizes that both men and women are entitled to equal respect and opportunities. In practice, the teaching on gender equality can be seen in the role of women who can become nuns and lead worship services. Even in social life, women can play an active role and work even as leaders in an organization.Kesetaraan gender tetap menjadi topik diskursus hangat untuk terus dikaji dan selalu berkaitkan dengan ajaran agama, termasuk juga agama Buddha. Sang Buddha mengajarkan bahwa perempuan dapat berperan aktif dalam ritual keagamaan dan aktivitas sosial. Namun, spekulasi pemuka maupun umat Buddha sendiri meletakkan perempuan dalam urutan kedua dan lebih rendah dari laki-laki. Karena itu, artikel ini fokus untuk menjelaskan bagaimana kesetaraan gender dalam perspektif ajaran Buddha dan bagaimana eksistensi Bhikkhuni di Vihara Dharmakirti Palembang. Penelitian lapangan ini menggunakan interview, observasi dan dokumentasi untuk mendapatkan data yang diperlukan. Hasil penelitian ini menunjukkan bahwa konsep ajaran gender dalam ajaran Buddha tidak tertuang dalam bentuk teks yang jelas tetapi ajaran kasih yang universal menjadi pedoman. Ajaran tentang kasih kepada semua makhluk terutama manusia, mempertegas bahwa baik laki-laki maupun perempuan berhak mendapatkan penghormatan dan kesempatan yang sama. Dalam praktiknya ajaran tentang kesetaraan gender itu terlihat pada peran perempuan yang dapat menjadi Bhikkhuni dan memimpin kebaktian. Dalam kehidupan sosial pun, perempuan dapat berperan aktif dan berkarya bahkan sebagai pemimpin dalam sebuah organisasi.